The effect of pretreatment of Broccoli (Brassica oleracea L. var. botrytis L.) to rifampicin pharmacokinetics in rats - Wahyono, Djoko; Hakim, Arief Rahman (Indonesian Journal of Pharmacy, 2005)
Consuming the meal during drug therapy could influence on pharmacokinetics profile of the drugs. The research was aimed to observe broccoli (Brassica oleracea L. var. botrytis L.) activities to rifampicin pharmacokinetics in rats. The study of interaction broccoli with rifampicin pharmacokinetics was conducted employing a completely randomaized design using female Sprague Dawley rats which were divided into 3 groups (6 rats for each group). The results have shown that the pharmacokinetics values of rifampicin in the animals prefed with broccoli 23.43 mg/kg BW 1 hours prior to single oral administration of the drug (P-II) did not change significantly (P>0.10). Prefeeding the animals with broccoli 23.43 g/kg BW once daily for 7 consecutive days (P-I) has increased the total clearance of rifampicin 46.90% (P